PENGGUNAAN KOMPOSIT KARET ALAM-ARANG AKTIF-PASIR COR UNTUK MENGURANGI KANDUNGAN NITRAT DALAM LARUTANNYA - Dyah Ayu Anggraini; Tengku Ariful Amri; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Composite is a material made up of two parts, binder (matrix) and filler. This material is widely used in human activities  as water purification media. Composite materials  that used in this study consist of natural rubber as a matrix with filled activated charcoal and sand cast. The composition of the composite is 0% sand  : 100% charcoal (KA), 50% sand : 50% charcoal (KAP), 100% sand : 0%  charcoal (KP). These composites are used to reduce the nitrate content in the nitrate solution  which  have  initial concentration of 5 and 10 ppm. Nitrate contents  before and after passing the composite were analyzed using Brusin sulfate  method. The results showed that the composite rail is more effective at reducing nitrate solution which has initial concentration of 10 ppm at 30o C. In these conditions the composite KA can  reduce the high nitrate content  to 73.38%, while the KAP and KP  can  only reduce nitrate  content  of 69.75% and 53.88% respectively.